Tungsten and Rhenium as Hydrogenation Agents in the Hydrodenitrogenation of Pyridine Using Stacked Bed Catalyst Systems - Gil-Llambias, F; Villarroel-Jorquera, M; Villarroel-Jorquera, M (Sociedad Chilena de Quimica, 2015)
This study analyses the hydrodenitrogenation (HDN) of pyridine using a stacked bed catalyst system, composed of a first hydrogenating bed of Re/γ-Al2O3 or W/γ-Al2O3, over a second bed of Ni-Re/γ-Al2O3 (HDN bed). Using potentiometric methods, it can be seen that the Re/γ-Al2O3 shows higher acidic strength than the W/γ-Al2O3. The results show that higher activity levels are obtained working with stacked bed systems compared to the separate catalysts. These results suggest that the incorporation of the catalyst Re/γ-Al2O3 or W/γ-Al2O3 beds would favour the formation of hydrogenated intermediary products, facilitating the removal of N-containing molecules via HDN on the Ni-Re/γ-Al2O3 catalyst.